Association between Storage Time of Corneal Grafts and Primary Graft Failure in Penetrating Keratoplasty: Doi: 10.36351/pjo.v40i3.1808 - Mushafia Hassan; Zafar Ali, Humera; Sidrah Latif; Jahangir, Ramsha; Jamal, Samreen (Pakistan Journal of Ophthalmology, 2024)
Purpose: To determine association between storage time of corneal grafts and primary graft failure in Penetrating Keratoplasty (PK). Study Design: Quasi experimental study. Place and Duration of Study: Institute of Ophthalmology, Eye Unit-III, King Edward Medical University, Mayo Hospital, Lahore from June, 2019 to December, 2019. Methods: In this study, 120 patients (between 11 and 30 years of age) diagnosed with keratoconus were enrolled and divided into two groups. Group A comprised individuals who underwent PK with donor tissues stored for 8 to 14 days, while Group B consisted of patients whose donor tissues were stored for a duration not exceeding 7 days. Patients were followed up for three weeks post-operatively. The data was analyzed using SPSS version 19 and stratified for age, gender and primary graft failure. Post stratification RR was calculated with p-value ≤ 0.05 as significant. Results: The mean age of patients in Group A was 21.38 ± 6.29 years and in Group B was19.80 ± 5.81 years. In Group A there were 32 male and 28 female while in Group B there were 29 male and 31 female. In Group A 16(26.7%) patients and in group B, 4 (6.7%) patients had primary graft failure. The risk of primary graft failure was higher in Group A, with RR = 4, p-value < 0.05. Conclusion: The risk of primary graft failure in PK is higher when the storage time of corneal grafts is longer. Hence, minimization of storage time may ensure better success rate of corneal grafting.